Implementasi Penyaluran Paket Online Shop Menggunakan Algoritma FIFO dan Dijkstra - Triase Triase; Rima Aprilia (Query: Journal of Information Systems, 2020)
In Indonesia, the number of online shoppers has continued to increase in recent years. Online purchasing activities in 2016 were only 9.6%, 2017 to 10.7%, while it is estimated that in 2018 it will be 11.9%. This growth has resulted in a high level of competition for goods or package distribution services. The high interest of online shoppers certainly makes the distribution service company of objects or packages very busy in serving online shops and online shoppers, resulting in queues of objects or packages at distribution service warehouses. The FIFO method is one of the queuing algorithms for processing queued goods in the warehouse and coupled with the Dijkstra method which functions to search for graphics that solve the problem of the path or shortest route from the courier to the address of the intended online shopper. Its application is expected to be able to optimize the performance of the distribution of objects or packages to online shoppers so that they can compete and increase profits. Keywords: online shop, packages, fifo, dijkstra, vb.net